Photo-Induced Coupled Nuclear and Electron Dynamics in the Nucleobase Uracil - Bäuml, Lena; Schnappinger, Thomas; Kling, Matthias F.; de Vivie-Riedle, Regina (Frontiers in Physics, 2021)
Photo-initiated processes in molecules often involve complex situations where the induced dynamics is characterized by the interplay of nuclear and electronic degrees of freedom. The interaction of the molecule with an ultrashort laser pulse or the coupling at a conical intersection (CoIn) induces coherent electron dynamics which is subsequently modified by the nuclear motion. The nuclear dynamics typically leads to a fast electronic decoherence but also, depending on the system, enables the reappearance of the coherent electron dynamics. We study this situation for the photo-induced nuclear and electron dynamics in the nucleobase uracil. The simulations are performed with our ansatz for the coupled description of the nuclear and electron dynamics in molecular systems (NEMol). After photo-excitation uracil exhibits an ultrafast relaxation mechanism mediated by CoIn's. Both processes, the excitation by a laser pulse and the non-adiabatic relaxation, are explicitly simulated and the coherent electron dynamics is monitored using our quantum mechanical NEMol approach. The electronic coherence induced by the CoIn is observable for a long time scale due the delocalized nature of the nuclear wavepacket.